Analisis Kelayakan Usaha Tahu AS Ditinjau Dari Aspek Produksi, Pemasaran dan Keuangan - Atikah Atikah; Tiara Tiara; Sri Hartini (Komunitas Dosen Indonesia, 2023)
Tofu factories are one of the small and medium businesses that can be developed, because tofu products are consumed by the wider community. The tofu factory has a good role in society, apart from being able to fulfill the community's need for high-protein foodstuffs, it can also provide employment opportunities for residents around the factory. This research was conducted in one of the tofu industries where this industry is still classified as MSMEs. This research aims to analyze the tofu business in order to find out whether the business is profitable or not, as well as to examine the commercial potential of tofu with the aim that this business will not only run well but can also develop so that it has good benefits from the point of view of production, marketing and finance. This analysis uses a method by looking at non-financial and financial aspects. Non-financial aspects are production and marketing aspects and continued with financial aspects. From the production aspect, it can be concluded that this Tofu Factory is worthy of development because it has been successful in producing tofu since 2001 with a production volume of around 3000 pcs of tofu per day. If viewed from a marketing aspect, this factory can be said to be feasible because its strategic location means that this tofu factory does not need to spend too much capital in terms of marketing, word of mouth marketing is enough to make this tofu factory known to the local community. From the financial aspect, it can be concluded that the US Tofu business is worthy of development based on the speed of capital return or payback period and PI.